2021
DOI: 10.1016/j.ygyno.2021.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of recurrence and survival in vulvar cancer: A nationwide population-based study

Abstract: In this nationwide population-based cohort, the overall recurrence rate was 22.3%.• The 5-year cumulative incidence rate for isolated local recurrence was only 14.7%.• Median 4-year overall survival post local recurrence was poor, 37.4%.• Surgical groin staging was omitted in 23.7% of FIGO stages IB-II.• Omitting surgical groin staging in FIGO stages IB-II was significantly associated with poor survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Although our understanding of VSCC carcinogenesis has progressed, treatment options for VSCC patients have not significantly evolved over the years [ 13 , 14 ]. The mainstay of VSCC treatment remains surgery with tumor-free resection margins, confirmed on microscopy [ 13 , 14 , 15 ]. Unfortunately, surgical interventions in the vulva may injure adjacent vital structures such as the urethra or the anus, resulting in post-operative morbidity and a reduced quality of life [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although our understanding of VSCC carcinogenesis has progressed, treatment options for VSCC patients have not significantly evolved over the years [ 13 , 14 ]. The mainstay of VSCC treatment remains surgery with tumor-free resection margins, confirmed on microscopy [ 13 , 14 , 15 ]. Unfortunately, surgical interventions in the vulva may injure adjacent vital structures such as the urethra or the anus, resulting in post-operative morbidity and a reduced quality of life [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although in literature it was described that lymphnode metastasis was the most significant factor, in our study, lymph node metastasis was not found to be statistically significant for recurrence (Figure 1) . Zach et al reported the recurrence rate as 22.3% in their study [12]. They also reported that stage 1 patients had an excellent prognosis.…”
Section: Discussionmentioning
confidence: 84%
“…Previous studies reported that the recurrence rate of vulvar cancer ranged from 14.5% to 21.2%, whereas the complication rate was 7.7% to 57.4% after vulvar reconstruction 11,13,18,24,25 . Because of the reconstruction uses the surrounding tissue, vulvar cancer showed a relatively higher recurrence rate in vulvar reconstruction.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies reported that the recurrence rate of vulvar cancer ranged from 14.5% to 21.2%, whereas the complication rate was 7.7% to 57.4% after vulvar reconstruction. 11,13,18,24,25 Because of the reconstruction uses the surrounding tissue, vulvar cancer showed a relatively higher recurrence rate in vulvar reconstruction. In addition, it showed a high surgical complication rate because the surgical site was a weight bearing site in the sitting position and a site where urine and feces is discharged.…”
Section: Discussionmentioning
confidence: 99%